Parental age effects on odor sensitivity in healthy subjects and schizophrenia patients. Issue 4 (29th July 2015) - Malaspina, Dolores; Walsh‐Messinger, Julie; Antonius, Daniel; Dracxler, Roberta; Rothman, Karen; Puthota, Jennifer; Gilman, Caitlin; Feuerstein, Jessica L.; Keefe, David; Goetz, Deborah; Goetz, Raymond R.; Buckley, Peter; et al.
Abstract : A schizophrenia phenotype for paternal and maternal age effects on illness risk could benefit etiological research. As odor sensitivity is associated with variability in symptoms and cognition in schizophrenia, we examined if it was related to parental ages in patients and healthy controls. We tested Leukocyte Telomere Length (LTL) as an explanatory factor, as LTL is associated with paternal age and schizophrenia risk. Seventy‐five DSM‐IV patients and 46 controls were assessed for detection of PEA, WAIS‐III for cognition, and LTL, assessed by qPCR. In healthy controls, but not schizophrenia patients, decreasing sensitivity was monotonically related to advancing parental ages, particularly in sons. The relationships between parental aging and odor sensitivity differed significantly for patients and controls (Fisher's R to Z: χ 2 = 6.95, P = 0.009). The groups also differed in the association of odor sensitivity with cognition; lesser sensitivity robustly predicted cognitive impairments in patients (<0.001), but these were unassociated in controls. LTL was unrelated to odor sensitivity and did not explain the association of lesser sensitivity with cognitive deficits.Parental aging predicted less sensitive detection in healthy subjects but not in schizophrenia patients. In patients, decreased odor sensitivity strongly predicted cognitive deficits, whereas more sensitive acuity was associated with older parents. These data support separate risk pathways for schizophrenia. A parental age‐related pathway may produce psychosis without impairing cognition and odor sensitivity. Diminished odor sensitivity may furthermore be useful as a biomarker for research and treatment studies in schizophrenia. © 2015 Wiley Periodicals, Inc.